Effect of Entrepreneurship Education and Family Environment on Entrepreneur Attitude and Interest of Science Teacher Candidates - Dadang Warta Chandra Wira Kusuma; Baiq Mirawati; Agus Muliadi (Postgraduate, University of Mataram, 2023)
This study aims to describe science teacher candidates’ perceptions of effect of entrepreneurship education and family environment on entrepreneur attitude and interest. This study is an exploratory research with 56 biology education students as respondents. The research instrument used was a closed questionnaire with degraded answers according to a Likert scale that had been validated by experts and declared valid. Analysis of research data used is descriptive quantitative statistics and inferential statistics with multiple linear regression test at a significance level of 5%. The results of the study show that ((1) perceptions of science teacher candidates towards entrepreneurship education have an average at 3.45 in good category, family environment at 2,73 in good category, entrepreneur attitude at 3,13 in good category, and entrepreneur interest at 3,08 in good category; (2) there is an effect of entrepreneurship learning and family environment on student entrepreneurial attitudes with a significance value of is smaller than the alpha testing value of 0,003 (<0,05); (3) there is an effect of entrepreneurship learning and family environment on entrepreneur interest with a significance value of 0.022 is smaller than the alpha testing value of 0,05 (<0,05); (4) entrepreneurship learning and family environment influence student entrepreneurial attitudes by 19,3% and the rest are influenced by variables or other factors; (5) entrepreneurship learning and family environment influence student entrepreneurial interest by 13,4% and the rest are influenced by variables or other factors.